PROFESIONALISME HOUSEMAN DALAM PENGUASAAN ALAT MESIN DI PUBLIC AREA HOTEL GRAND CENTRAL PEKANBARU - Sukmana, Muhammad Davis; Sulistyani, Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Hotel development in Pekanbaru is growing very rapidly and become the main industry which was very promising for entrepreneurs of hospitality services. Thus,the quality of services were to be something very important because costumers always need to get what the best presence of the service provided. It has been consequensed on the need of employee, especially the houseman, to subscrib on the guidance and requirements of Standar Operasional Prosedur (SOP) as demanded on professionalism.This study aims to determine the level of houseman professionalism in Grand Central Hotel Pekanbaru.In the study the researcher uses a mix methods of both qualitative and quantitative as the research procedure that generated the data in the form of interview ,documentation, observation and questionnaire. In this case, there were 8 respondents and several informant, including 1 Supervisor, 1 F& B Manager, 1 HRD, and 8 houseman for interview.As the conclusion, the professionalism of Public Area Section houseman was categorized as in good level regarding the result of 77,8% point in questionaires analysis.Key words : profesionalism, houseman, public area, machine tools